Short-wave visible polarization detector based on one-dimensional GaS nanobelt and preparation method thereof
Growing one-dimensional GaS nanoribbons through CVD and preparing short-wave visible polarization photodetectors is solved, which lacks polarization response capabilities of traditional GaS materials, and achieves efficient polarization imaging of small-size pixels.
Patent Information
- Application Number
- CN202411844079.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-15
AI Technical Summary
Traditional GaS materials lack polarized light response capabilities due to their in-plane symmetry, which limits their application in the field of light detection.
By growing one-dimensional GaS nanoribbons through CVD, combined with fixed-point ultraviolet lithography techniques and precise transfer technology, a short-wave visible polarization photodetector based on one-dimensional GaS nanoribbons was prepared.
Polarization imaging of small-sized pixels is realized, and polarization detection can be performed under short-wave visible light (405nm), with considerable response speed and high responsiveness, and is suitable for clear polarization imaging of small-sized pixels.
Smart Images

Figure CN119698122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of nano-functional materials, photoelectric detection and aerospace technology, and specifically relates to a short-wave visible polarization photoelectric detector based on a one-dimensional GaS nanoribbon and a preparation method thereof. Background Art
[0002] Polarization photodetectors are advanced light detection devices that can not only measure the intensity and wavelength of light, but also detect the polarization state of light. This type of detector can improve the imaging quality and the ability to identify objects, so it has broad application prospects in many high-tech fields. Polarization imaging technology has become a hot topic in the field of photoelectric detection technology since the Discovery space shuttle conducted its first polarization imaging observation of the Earth in 1984. Compared with non-polarization imaging detection, polarization imaging can extract the Stokes vector of the target image, thereby obtaining the polarization angle and polarization degree image of the target spectrum, and can perform clear imaging in environments such as thick clouds, haze, and dust, making it have obvious advantages in observing target details, suppressing background noise, and increasing observation distance. Traditional polarization photodetectors usually require complex optical path design, such as using optical elements such as polarizers and lenses, or using polarization encoding systems to achieve sensitive detection of polarized light. However, this design often results in the detector being bulky, expensive, and complex in structure, limiting its scope of application. Recently, scientists have discovered that low-dimensional nanomaterials have great potential in the field of polarization photoelectronic devices. The optical and electrical properties of these materials are anisotropic in the plane, which means that they can respond differently to polarized light in different directions. Using these materials, smaller, lower-cost, and simpler polarized photodetectors can be designed, which promotes the miniaturization and integration of polarized photoelectric systems. Gallium sulfide (GaS), a semiconductor material with indirect bandgap characteristics, has attracted much attention in the field of ultraviolet-shortwave visible photodetection due to its ultra-wide bandgap, good environmental tolerance, and suitable preparation cost. However, due to the in-plane symmetry of traditional gallium sulfide, its inherent structure does not have the ability to respond to polarized light. Therefore, it is urgent to find effective strategies to expand the application scope of GaS in the field of light detection, realize polarized light detection technology based on GaS structure, and then realize large-scale controllable production. The existing technology urgently needs further improvement and innovation. Summary of the invention
[0003] The purpose of the present invention is to solve the problem of the lack of polarized light influence characteristics caused by the in-plane symmetry of traditional GaS, and to provide a one-dimensional GaS nanoribbon material and a short-wave visible polarization detector based on the one-dimensional GaS nanoribbon and a preparation method thereof.
[0004] The one-dimensional GaS nanobelt material is prepared by the following method: the growth source GaS powder is placed at the front end of the quartz tube of the muffle furnace, and the SiO2 / Si substrate is placed at the rear end. Ar / H2 is introduced into the tube furnace, and the growth source GaS powder is heated at 830-850°C for 7 minutes. A plurality of one-dimensional GaS nanobelt materials gather on the substrate. The PDMS film with double-sided adhesiveness is used for precise pasting and separation to obtain a one-dimensional GaS nanobelt material.
[0005] The distance between GaS powder and SiO2 / Si substrate is 12-14 cm;
[0006] The heating method is to first raise the furnace temperature from room temperature 25°C to 700°C for 20 minutes, and after the furnace is preheated, set the temperature to 840°C for 16 minutes. When the temperature is raised to 820°C, the central temperature zone of the muffle furnace is moved to the position of the growth source GaS powder, and the Ar flow rate is adjusted to 55sccm; when the growth temperature reaches 840°C, the H2 flow rate is increased to 35sccm; the Ar flow rate is adjusted to 55sccm; when the growth temperature reaches 840°C, the H2 flow rate is increased to 35sccm; the two-dimensional multiple GaS nanobelts are successfully grown; stop introducing H2, increase the Ar flow rate to 80sccm, exhaust H2, move the heating temperature zone away from the growth source, and take it out after cooling.
[0007] The SiO2 / Si substrate is ultrasonically cleaned with trichloroethylene, acetone, isopropanol, ethanol and deionized water in sequence, and blown dry with nitrogen for later use; the ultrasonic power is 80W and the ultrasonic time is 10min.
[0008] A short-wave visible polarization photodetector of a one-dimensional GaS nanobelt is provided with two electrodes and a one-dimensional GaS nanobelt material on a SiO2 / Si substrate; the two electrodes are respectively deposited on both sides of the one-dimensional GaS nanobelt material by a vacuum thermal evaporation coating method;
[0009] The one-dimensional GaS nanoribbon material is prepared by the method of claim 1;
[0010] The electrodes are gold electrodes, and the channel interval between the two electrodes is 5 μm.
[0011] A method for preparing a short-wave visible polarization detector based on a one-dimensional GaS nanoribbon comprises the following steps:
[0012] S1: Transferring one-dimensional GaS nanobelt material: placing a SiO2 / Si substrate on a two-dimensional material transfer platform, and accurately sticking a one-dimensional GaS nanobelt material as claimed in claim 1 with a double-sided sticky PDMS film; transferring it to the center of the SiO2 / Si substrate, heating the platform, lifting the PDMS that loses its stickiness, vacuum heating the SiO2 / Si substrate with the attached sample to 120°C, annealing, and cooling to room temperature;
[0013] S2: Electrode fabrication: Spin-coat photoresist on the SiO2 / Si substrate with the one-dimensional GaS nanobelt material attached, and dry at 120°C; perform point-to-point UV exposure, development, and nitrogen drying after alignment; vacuum evaporation coating, remove the glue, and prepare two symmetrical electrodes on both sides of the one-dimensional GaS nanobelt material;
[0014] S3: Heat at 100°C in vacuum for 2 h and cool to room temperature to obtain a short-wave visible polarization detector based on one-dimensional GaS nanoribbons.
[0015] The present invention adopts the method of breaking the in-plane optical isotropy by growing one-dimensional materials by CVD, and successfully prepares a short-wave visible polarization photodetector based on one-dimensional GaS nanoribbons based on fixed-point UV lithography and precise transfer technology, realizing polarization imaging of small-size pixels. Polarization detection can be performed under short-wave visible (405nm) laser irradiation, with considerable response speed and high responsivity, and clear small-size pixel polarization imaging can be performed. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The figure is a schematic diagram of the preparation process of the one-dimensional GaS nanoribbon short-wave visible polarization photodetector of the present invention;
[0017] Figure 2 The schematic diagram of the design of the short-wave visible polarization photodetector of the one-dimensional GaS nanoribbon of the present invention;
[0018] Figure 3 An optical microscope image and an AFM thickness diagram of a one-dimensional GaS nanoribbon of the present invention;
[0019] Figure 4 TEM transmission electron microscope images of the one-dimensional GaS nanoribbon of the present invention, (a) top view, (b) side view;
[0020] Figure 5 Schematic diagram of the atomic structure of the one-dimensional GaS nanoribbon of the present invention;
[0021] Figure 6 This is a polarized Raman spectrum of the one-dimensional GaS nanoribbon of the present invention;
[0022] Figure 7 This is a photoelectric detection diagram of the short-wave visible polarization photodetector of the one-dimensional GaS nanoribbon of the present invention;
[0023] Figure 8 This is a polarization photoelectric detection diagram of the short-wave visible polarization photoelectric detector of the one-dimensional GaS nanoribbon of the present invention;
[0024] Fig. 9 This is a polarization photoelectric detection diagram of the short-wave visible polarization photoelectric detector of the one-dimensional GaS nanoribbon of the present invention under variable pressure;
[0025] Fig.10 This is a photoluminescence spectrum of the one-dimensional GaS nanoribbon of the present invention;
[0026] Fig.11 This is a schematic diagram of polarization imaging principle of the short-wave visible polarization photodetector of the one-dimensional GaS nanoribbon of the present invention;
[0027] Fig.12 Schematic diagram of polarization imaging of the short-wave visible polarization photodetector of the one-dimensional GaS nanoribbon of the present invention. DETAILED DESCRIPTION
[0028] Example 1
[0029] The method for growing GaS nanoribbons based on CVD chemical vapor deposition method includes the following steps:
[0030] Step 1: Weigh 7 mg of GaS powder and place it in the center of quartz boat 1;
[0031] Step 2: Make the base substrate:
[0032] The single-sided Si and 300nm SiO2 N-type substrate of Hefei Kejing Material Technology Co., Ltd. were used as the base material. The wafer-level SiO2 / Si substrate was precisely cut using a fiber laser marking machine with a laser power of 90%, a cutting speed of 20mm / s, and a cutting frequency of 20kHz. The substrate was cut to a size of 1cm*1cm.
[0033] Step 3: Place the clean substrate in quartz boat 2 with the SiO2 surface facing upward; place quartz boat 2 on the right side of quartz boat 1 and push it into the quartz tube of the muffle furnace so that the GaS powder is 13 cm away from the clean substrate, and introduce Ar gas at a flow rate greater than 80 sccm to exhaust the air;
[0034] Step 4: Set the temperature program: First, raise the furnace temperature from room temperature 25℃ to 700℃ in 20 minutes. After the furnace is preheated, set it to heat up to 840℃ in 16 minutes. When the temperature reaches 820℃, move the center temperature zone of the muffle furnace to the position of the growth source GaS powder. Figure 1 Red area;
[0035] Step 5: The Ar flow rate is adjusted to 55 sccm; when the growth temperature reaches 840°C, the H2 flow rate is increased to 35 sccm;
[0036] Step 6: Wait for 7 minutes to successfully grow multiple two-dimensional GaS nanoribbons;
[0037] Step 7: Stop the H2 flow, increase the Ar flow rate to 80 sccm, exhaust the H2, move the heating temperature zone away from the growth source, cool it down, and take out the grown substrate with multiple nanowires for use.
[0038] Example 2
[0039] A method for preparing a short-wave visible polarization photodetector based on a one-dimensional GaS nanoribbon comprises the following steps:
[0040] Step 1: Prepare a clean base substrate;
[0041] Step 2: Transfer and make one-dimensional GaS nanosheet material, see attached Figure 1 :
[0042] 1) Take a large number of one-dimensional GaS nanosheets prepared by CVD, with a thickness of about 100nm;
[0043] 2) Place the substrate with multiple one-dimensional GaS nanosheets on the two-dimensional material transfer table and use a 0.25 cm 2 One side of the double-sided adhesive PDMS film is pasted on a glass slide, and the other side is precisely pasted with nanosheets with excellent morphology in the corners with the help of a microscope. After compaction, the nanosheets are lifted up and brought onto the PDMS. During the process, the transfer table is kept slightly tilted to ensure that only the required nanosheets are picked up on the PDMS.
[0044] 3) Place a clean substrate on a two-dimensional transfer table, keep the tabletop level, and drop the PDMS with nanosheets onto the SiO2 / Si substrate precisely through a microscope. After compaction, heat the platform to 80°C at 2°C / min and keep it for ten minutes. The PDMS is deactivated and lifted, and the nanosheets fall onto the SiO2 / Si substrate.
[0045] 4) Vacuum anneal the substrate with the attached sample, that is, place the sample in a vacuum quartz tube and heat it to 120℃ at 3℃ / min, then anneal for 1h, and then cool it to room temperature at 3℃ / min. Figure 3 ,The successfully transferred nanoribbons were about 1 micron wide, about 120nm thick, and longer than 50 microns;
[0046] Step 3: Making the electrodes:
[0047] 1) Under yellow light environment, a uniform layer of photoresist film is formed by two-step spin coating on the SiO2 / Si substrate containing GaS nanosheets on the surface, and a UV exposure lithography method is used to construct the following Figure 2 The electrode shown (photoresist AZ-5214, exposure energy 180mJ / cm 2 );
[0048] 2) The process parameters of the two-step spin coating of photoresist are: the first step speed is set to 600 rad / s, the time is 6s; the second step speed is set to 4000 rad / s, the time is 30s;
[0049] 3) Bake the spin-coated wafer at 120°C for 90 seconds, and then align the drawing and the nanowire sample for UV exposure;
[0050] 4) After 60 seconds of development, the position where the electrode needs to be prepared is exposed by exposure, and a 50 nm Au layer is deposited by vacuum thermal evaporation coating. The photoresist is removed by acetone cleaning. The obtained device is heated at 100° C. in vacuum for 2 hours and cooled to room temperature to obtain the polarization photodetector, wherein the GaS position exposed between the two electrodes is the channel material;
[0051] In the detector of the present invention, GaS nanobelt is used as a photoconductive material to realize photoelectric conversion. Two symmetrical electrodes are respectively located at the two ends of the nanobelt and remain perpendicular. The photogenerated carriers generated by light excitation are transmitted to the symmetrical electrodes at the two ends. The electrodes at the two ends are externally connected to a source meter, and the generation of photocurrent can be observed, which is further used for the detection of polarized light.
[0052] Example 3
[0053] Polarization imaging system optical path construction and testing method
[0054] 1) See attached Fig.12 The linearly polarized laser passes through a half-wave plate and a scattering medium (ground glass is used in the present invention) and then irradiates a circular mask (1 cm in diameter). After passing through the mask, it irradiates a short-wave visible polarization photodetector based on a one-dimensional GaS nanoribbon.
[0055] 2) Use a two-dimensional mobile platform to move the mask at a speed of 0.5 mm / s to simulate a multi-array detection mode and image the mask.
[0056] 3) Rotating the half-wave plate changes the polarization direction of different incident light, which is equivalent to rotating the sample and is conducive to achieving DOLP polarization imaging.
[0057] Performance Characterization of Short-wavelength Visible Polarized Photodetector Based on One-dimensional GaS Nanoribbons
[0058] See also Figure 4 , 5 As shown in the figure, the large-diameter atom is Ga and the small-diameter atom is S. The TEM and atomic structure model of GaS show that GaS is a layered semiconductor material, each layer of which is composed of Ga-SS-Ga repeating units. The TEM top view shows that there is a stable hexagonal structure in the z direction. The material has good crystal quality and belongs to the hexagonal system. The Ga and S atoms in the GaS layer are connected by covalent bonds, while the interlayer coupling is achieved through van der Waals forces. From the TEM image, it can be seen that the cross-section of the one-dimensional GaS nanobelt prepared by CVD shows an ABC stacking mode, which is consistent with the γ phase arrangement. Fig.11It can be seen from the photoluminescence graph that the optical band gap of GaS is 2.53eV, which makes GaS layered materials can be used to manufacture short-wave visible light photodetection devices; GaS with indirect band gap does not have good luminescence characteristics, and the photoluminescence peak is weak. However, GaS has good light absorption and good photoconductivity. This photoconductivity is manifested in that under the irradiation of certain specific wavelengths of light, the conductivity of the material is different from the conductivity in the dark state; because the photoconductive material can absorb energy under laser induction to generate a large number of photogenerated carriers, thereby promoting the conductive effect and improving the conductivity of the material, GaS as a group III transition metal monochalcogenide is a better photoconductive material. Traditional two-dimensional GaS materials have in-plane symmetry, and the intrinsic GaS structure has no polarized light response characteristics. Based on this, an embodiment of the present invention provides a short-wave visible polarization photodetector based on a one-dimensional GaS nanoribbon, so as to further expand the application of GaS in the field of light detection and realize polarization imaging based on GaS nanostructures. The prepared one-dimensional GaS nanoribbon photodetector can use a source meter and a probe to perform a series of basic photoelectric and polarization photoelectric tests on the Au evaporated at both ends;
[0059] In order to identify the optical anisotropy of the selected material due to the one-dimensional geometric structure breaking the in-plane optical isotropy, the one-dimensional GaS nanoribbon material was tested by angle-resolved polarized Raman spectroscopy: three vibration modes of GaS were detected: E 2g 1 ,A 1g 1 , and A 1g 2 , corresponding to wave number 304cm -1 , 188cm -1 , 359cm -1 , where A 1g The mode peak changes periodically with the angle, showing good optical anisotropy. Figure 6 shown.
[0060] The photoluminescence spectrum was also collected using a 320nm laser. The results are shown in the figure. The luminescence peak is around 490nm. It can be inferred from the band gap that the material is a multilayer structure. Figure 3 It can be seen that the thickness of the material is about 120nm (the thickness of a single layer of GaS material is less than 1nm).
[0061] Under 405nm laser irradiation, the IV curve is measured as shown in the attached figure. Figure 7. From the curve, it can be seen that the device is turned on and the photocurrent is at the nanoampere (nA) level. When tested at high voltage (5V), a strong photocurrent can be clearly observed, because the external bias electric field accelerates the separation of electrons and holes, and as the excitation light power increases, the photocurrent also increases. The IT curve shows that the photocurrent has increased by an order of magnitude, the light and dark currents are clearly distinguished, and the response speed reaches the ms level.
[0062] In order to explore the performance of one-dimensional GaS nanosheet polarization photodetector, the present invention tests the polarization light response of the detector for various lasers in the visible band, among which the polarization response under 405nm laser is the strongest, as shown in the attached figure. Figure 8 After multiple tests, see the attached Figure 8 When 1.5V is selected as the bias voltage, a higher polarization ratio of 1.25 can be achieved; when 5V is selected as the bias voltage, a lower dark current and a larger on / off ratio (~10 3 ) and a relatively excellent polarization ratio.
[0063] Under the above conditions, the optical path constructed in Example 2 was used to apply the one-dimensional GaS nanosheet polarization photodetector to achieve polarization imaging under short-wave visible light. The effect diagram is shown in FIG. Fig.10 .
[0064] It should be noted that the application of the present invention is not limited to the above examples. As a photoconductive material for emerging photodetectors, GaS can capture the intensity and wavelength signals of light. Among them, artificially induced anisotropy, such as the introduction of metal antennas, stress-induced introduction, and nanobelt processing used in the present invention, can all improve the polarization detection performance index of the prepared device, that is, the anisotropy ratio. The present invention is expected to achieve large-scale controllable production to form an array-type polarization imaging element.
Claims
1. One-dimensional GaS nanobelt material is prepared by the following method: Take the growth source GaS powder and place it at the front end of the quartz tube of the muffle furnace, and place the SiO2 / Si substrate at the rear end. Ar / H2 is introduced into the tube furnace. The growth source GaS powder is heated at 830-850°C for 7 minutes, and multiple one-dimensional GaS nanobelt materials gather on the substrate; use a double-sided adhesive PDMS film to precisely stick and separate to obtain a one-dimensional GaS nanobelt material.
2. The one-dimensional GaS nanoribbon material according to claim 1, characterized in that: The distance between GaS powder and SiO2 / Si substrate was 12-14 cm.
3. The one-dimensional GaS nanoribbon material according to claim 1 or 2, characterized in that: First, the furnace temperature is raised from room temperature 25°C to 700°C in 20 minutes. After the furnace is preheated, it is set to heat up to 840°C in 16 minutes. When the temperature reaches 820°C, the central temperature zone of the muffle furnace is moved to the position of the growth source GaS powder, and the Ar flow rate is adjusted to 55sccm; when the growth temperature reaches 840°C, the H2 flow rate is increased to 35sccm; the Ar flow rate is adjusted to 55sccm; when the growth temperature reaches 840°C, the H2 flow rate is increased to 35sccm; multiple two-dimensional GaS nanobelts are successfully grown; stop introducing H2, increase the Ar flow rate to 80sccm, exhaust H2, move the heating temperature zone away from the growth source, and take it out after cooling.
4. The one-dimensional GaS nanoribbon material according to claim 3, characterized in that: The SiO2 / Si substrate is ultrasonically cleaned with trichloroethylene, acetone, isopropanol, ethanol and deionized water in sequence, and blown dry with nitrogen for later use; the ultrasonic power is 80W and the ultrasonic time is 10min.
5. One-dimensional GaS nanoribbon short-wave visible polarization photodetector, characterized by: Two electrodes and a one-dimensional GaS nanobelt material are arranged on a SiO2 / Si substrate; the two electrodes are deposited on both sides of the one-dimensional GaS nanobelt material by a vacuum thermal evaporation coating method; The one-dimensional GaS nanobelt material is prepared by the method of claim 1.
6. The one-dimensional GaS nanoribbon short-wave visible polarization photodetector according to claim 5, characterized in that: The electrodes are gold electrodes, and the channel interval between the two electrodes is 5 μm.
7. A method for preparing a short-wave visible polarization detector based on a one-dimensional GaS nanoribbon, comprising the following steps: S1: Transferring one-dimensional GaS nanobelt material: placing a SiO2 / Si substrate on a two-dimensional material transfer platform, and accurately sticking a one-dimensional GaS nanobelt material as claimed in claim 1 with a double-sided sticky PDMS film; transferring it to the center of the SiO2 / Si substrate, heating the platform, lifting the PDMS that loses its stickiness, vacuum heating the SiO2 / Si substrate with the attached sample to 120°C, annealing, and cooling to room temperature; S2: Electrode fabrication: Spin-coat photoresist on the SiO2 / Si substrate with the one-dimensional GaS nanobelt material attached, and dry at 120°C; perform point-to-point UV exposure, development, and nitrogen drying after alignment; vacuum evaporation coating, remove the glue, and prepare two symmetrical electrodes on both sides of the one-dimensional GaS nanobelt material; S3: Heat at 100°C in vacuum for 2 h and cool to room temperature to obtain a short-wave visible polarization detector based on one-dimensional GaS nanoribbons.
Citation Information
Patent Citations
Grating monitoring system based on ribbon-shaped optical fiber
CN101216328A
Preparation method of germanium diselenide nano material
CN112456452A
Multi-polarization-state detection optical detector based on two-dimensional material and preparation method of multi-polarization-state detection optical detector
CN114639746A
Transition metal sulfide nanobelt with high orientation and adjustable edge structure and chirality
CN117448949A
High-anisotropy-ratio two-dimensional GaS polarized photoelectric detector and preparation method thereof
CN117690991A